1998
DOI: 10.1291/hypres.21.227
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Coronary Blood Flow and Left Ventricular Mass in Hypertension. Noninvasive Quantification of Coronary Blood Flow by Thallium-201 Myocardial Scintigraphy.

Abstract: This study was conducted to quantify coronary blood flow (CBF) noninvasively according to the fractionation principle and to elucidate the relation between CBF and left ventricular hypertrophy. CBF/ cardiac output (CO), estimated on the basis of the ratio of myocardial uptake/total injected dose of thallium-201(% cardiac uptake), was determined in 14 control subjects and 40 patients with essential hypertension. CBF and CBF per 100 g of myocardium (unit CBF) were calculated according to the following formulas: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 22 publications
1
22
1
Order By: Relevance
“…In our study, RWT was significantly correlated with-and LVMI tended to correlate with-the CFR, and the basal coronary flow in hypertensive patients was increased to the same degree as in previous studies (10,25). It has been suggested that remodeling of the coronary arterioles, an increase in the extracellular matrix, and increased oxygen demand following established LVH are all strong contributors to the impairment of CFR in patients with hypertension (26,27). However, when the analysis was limited to hypertensive patients in our study, CFR did not correlate with LVMI or RWT.…”
Section: Discussionsupporting
confidence: 82%
“…In our study, RWT was significantly correlated with-and LVMI tended to correlate with-the CFR, and the basal coronary flow in hypertensive patients was increased to the same degree as in previous studies (10,25). It has been suggested that remodeling of the coronary arterioles, an increase in the extracellular matrix, and increased oxygen demand following established LVH are all strong contributors to the impairment of CFR in patients with hypertension (26,27). However, when the analysis was limited to hypertensive patients in our study, CFR did not correlate with LVMI or RWT.…”
Section: Discussionsupporting
confidence: 82%
“…Eleven studies were identified and comprised the review of the effect of HTN on CBF in patients (Table ). Seven studies measured total blood flow and 4 measured flow in the left anterior descending coronary artery (LAD) . There were 318 persons with HTN and 185 controls.…”
Section: Resultsmentioning
confidence: 99%
“…In working skeletal muscle, blood flow and capillary permeability increase to reduce the concentration difference between arterial and interstitial glucose. The interstitial glucose concentration was surprisingly low, since the blood flow in the myocardium is much higher than in skeletal muscle, which, in turn, indicates that the cellular uptake of glucose in the myocardium is extremely efficient (5,10,41).…”
Section: Discussionmentioning
confidence: 99%